The Implementation of Restorative Justice to Mistreatment Crime In the North Gorontalo District Attorney's - Widyaningsih, Aryana Sekar; Istiqomah, Milda; Sugiri, Bambang (Jurnal Ius Constituendum, 2025)
The purpose of this research is to explain how the implementation and the obstacles to the implementation of Restorative Justice to mistreatment crime in North Gorontalo State Attorney. This research became interesting because the District Attorney's Office handled only 3-4 cases with the restorative justice mechanism caused by the social aspect. The urgency of this research is the potential of restorative justice to reduce the overcapacity of correctional institutions and reduce the rate of recidivism, which is a crucial problem in Indonesia. The research method used in this research is empirical juridical, where the author directly conducts interviews and observations. This research is unique because it deeply explores the perceptions of the parties involved in the implementation of restorative justice, an area that is still rarely researched. Based on the research obtained the results first, the application has been carried out by the guidelines. Second, the obstacles found were not achieving the element of peace and agreement, which was influenced by the views of the parties. The obstacles found were the possibility of overcapacity in correctional institutions and the development of criminal acts while in correctional institutions. So it can be concluded that the application of restorative justice implementation needs the awareness of the parties and its application, so the impact can help reduce overcapacity and recidivism in the future.